Exploring Blockchain as a Security Framework for IoT in Healthcare: A Systematic Literature Review - Lutviana; Iis Setiawan Mangkunegara; Hamzah M. Marhoon (Journal of Advanced Health Informatics Research, 2024)
This systematic literature review explores the use of blockchain technology to improve the security of communication between IoT devices in the healthcare sector. The integration of IoT in healthcare has revolutionized patient data management but introduced security challenges. Blockchain, as a decentralized and immutable ledger, offers a potential solution by providing a secure method of data storage and transmission. This review analyzed 62 relevant studies published in the last five years using the PRISMA methodology. The main contributions of blockchain include improved data security, privacy, and data integrity, with decentralization and cryptographic techniques ensuring patient data remains secure and accessible only to authorized entities. Challenges of blockchain implementation include interoperability, data storage efficiency, and the need for strong cryptographic algorithms. Proposed solutions include the development of a specialized blockchain framework for healthcare, the integration of advanced encryption methods, and the use of distributed ledger technology to manage electronic medical records. Further research is needed to develop more efficient and secure blockchain solutions in healthcare applications, including improved interoperability, encryption algorithms, and real-world case studies. Although challenges remain, blockchain has great potential to improve the communication security of IoT devices in the healthcare sector.